Glucose, C-peptide and Cortisol Response To Surgery Under General Anesthesia In Diabetic Subjects with Treatment Variability (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Diabetic patients are considered to be at increased risk of perioperative morbidity and mortality because of the involvement of their vital organs and the autonomic nervous system in the natural course of the disease. Various aspects of anesthesia and surgery cause stress induced hemodynamic, endocrine and metabolic changes in type 2 diabetic subjects. The present study was designed to investigate the surgical stress response difference between the patients groups those who are treated with only insulin and with insulin-oral hypoglycaemic drugs combination before surgery. Stress response was measured with the changes of blood glucose, C-peptide and cortisol. A total number of 30 subjects who were admitted in BIRDEM hospital in fit physical condition (ASA Class I & II) were selected for the present study. Among them 15 patients were treated with only insulin and 15 patients were treated with insulin- OHA combination before surgery. All of the subjects were received total abdominal hysterectomy under general anesthesia. Three samples were collected from each subject. The first sample (control, PT0) was collected just before anesthesia; second sample (PT1) collected 10 minutes after incision and third sample (PT2) collected 10 minutes after extubation. Plasma glucose was measured by glucose oxidase method, serum C-peptide and cortisol by chemiluminescent based ELISA technique. The mean±SD age and BMI were 44±6 years and 24.4±3.0 kg/m2 respectively. In insulin treated group, the plasma glucose level was significantly higher in PT2 and it was about 147% whereas in insulin-OHA group, the plasma glucose level was significantly higher in both PT1 (111%) and PT2 (196%). The serum C-peptide values were decreasing tendency but not significant in both groups. The serum cortisol level was increased gradually and significantly higher in PT2 in both groups. The data suggest that a) insulin treatment alone is more effective than insulin-OHA combination to control blood glucose in type 2 diabetic subjects undergoing surgery under general anesthesia, b) lower abdominal surgery under general anesthesia in well controlled type 2 diabetic subjects is accompanied by a hyperglycemic response which results from rise of insulin antagonists like cortisol rather than fall of insulin secretion, but the two treatment modalities lead to similar cortisol response. Key words: General anesthesia, Serum glucose, cortisol, Total abdominal hysterectomy Journal of BSA, Vol. 20, No. 1, January 2007 p.3-8